Both four-dimensional computed tomography and four-dimensional cone beam computed tomography under-predict lung target motion during radiotherapy. (June 2019) - Steiner, Elisabeth; Shieh, Chun-Chien; Caillet, Vincent; Booth, Jeremy; O'Brien, Ricky; Briggs, Adam; Hardcastle, Nicholas; Jayamanne, Dasantha; Szymura, Kathryn; Eade, Thomas; Keall, Paul
Highlights: 4DCT and 4DCBCT under-predict treatment lung target motion ranges. 4DCT under-predicts target motion by factors of 1.7–1.9 and 4DCBCT by factors of 1.5–1.6. 4DCBCT shows higher correlations with target motion than 4DCT. 4DCT and 4DCBCT motion measurements should be interpreted carefully. Abstract: Background and purpose: To test the hypothesis that 4DCT and 4DCBCT-measured target motion ranges predict target motion ranges during lung cancer SABR. Materials and methods: Ten lung SABR patients were implanted with Calypso beacons. 4DCBCT was reconstructed for 29 fractions (1–4fx/patient) from a 1 min CBCT scan. The beacon centroid motion segmented for all 4DCT and 4DCBCT bins was compared with the real-time imaging and treatment beacon centroid ("target") motion range (4SDs) for each fraction. We tested the hypotheses that (1) 4DCT and 4CBCT predict treatment motion range and (2) there is no difference between 4DCT and 4DCBCT for predicting treatment motion range. Phase-wise root-mean-square errors (RMSEs) between imaging and treatment motion and reconstructed motion (4DCT, 4DCBCT) were calculated. Relationships between motion ranges in 4DCT and 4DCBCT and imaging and treatment motion ranges were investigated for the superior–inferior (SI), left–right (LR) and anterior–posterior (AP) directions. Baseline drifts and amplitude variability were investigated as potential factors leading to motion misrepresentation. Results: SI 4DCT, 4DCBCT, imaging and treatment motion ranges were 6.3 ± 3.6 mm, 7.1 ± 4.5 mm, 11.1 ± 7.5 mm and 10.9 ± 6.9 mm, respectively. Similar 4DCT and 4DCBCT under-predictions were observed in the LR and AP directions. Hypothesis (1) was rejected ( p < 0.0001). Treatment target motion range was under-predicted in 4DCT by factors of 1.7, 1.9 and 1.7 and in 4DCBCT by factors of 1.5, 1.6 and 1.6 in the SI, LR, and AP directions, respectively. RMSEs were generally lower for end-exhale than inhale. 4DCBCT showed higher correlations with the imaging and treatment target motion than 4DCT and testing hypothesis (2) a statistically significant difference between 4DCT and 4DCBCT was shown in the SI direction ( p = 0.03). Conclusion: For lung SABR patients both 4DCT and 4DCBCT significantly under-predict treatment target motion ranges.